Phytopathogenic fungi of Caragana arborescens Lam., growing in the city Karaganda - Beisembay, A.Zh.; Ospanova, A.K.; Kali, A.; Eken, C. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article presents the results of the determination of powdery-mildews fungi and rust fungi of shrub plantings growing on the streets, squares and parks of the city of Karaganda. The article presents data on the species composition of phytopathogenic fungi, where the host-plant is the Caragana arborescens Lam., growing in the city of Karaganda. Theoretical and practical information on methods for determining phytopathogenic fungi by fruit bodies, appendages, asci and ascospores has been collected by us. Phytopathogenic fungi are directly dependent on their host-plant, the conditions of development and the duration of the period of vegetation. Timely study of the condition of the plants used for greening the city, identification of diseases, level of their development, distribution, biology in accordance with the climatic conditions of the region is the basis for preventing the spread of these harmful organisms, carrying out effective control measures against them. For the first time in this region, the shrub Caragana arborescens Lam. is a host-plant for such species of phytopathogenic fungi as: powdery-mildews fungi Microsphaera caraganae L., rust fungi Uromyces cytisi J. Schröt.
Қарағанды қаласында өсетін ағаш қараған Caragana arborescens Lam. фитопатогенді саңырауқұлақтары
Фитопатогенные грибы Караганы древовидной Caragana arborescens Lam., произрастающей в городе Караганде
Keywords: industrial city; shrub plantings; Caragana arborescens Lam; phytopathogenic fungi; powderymildews fungi; rust fungi; Microsphaera caraganae L; Uromyces cytisi J. Schröt